2018
DOI: 10.9734/afsj/2018/41040
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic Qualities of Ham of Weaner Pigs Fed Graded Levels of Sundried Cassava Peel Meal

Abstract: A twelve-week feeding trial was conducted to evaluate the effects of Cassava Peel Meal(CPM) on the organoleptic properties of ham of (24) crossbred weaner pigs allocated to four dietary treatments replicated three times in a Completely Randomised Design(CRD) with each replicates having two pigs. Treatment I had 0% CPM while 2, 3 and 4 had (CPM) of 25%, 50% and 75% respectively. The pigs were allowed free assess to feed and clean drinking water ad-libitum and routine management and medication were administered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…The inclusion of Moringa oleifera leaf powder and Allium sativum bulb powder into broiler chicken diet at the lowest level may not have the ability to affect the taste and aroma of the meat. This observation contrasted with the findings of Adomeh and Eguaoje (2019), who reported that high aroma score recorded in chicken thighs spiced with 1.5 % ginger and garlic easily influenced the broiler meat. The meat tenderness at the 8 th week was improved in T3 and T4 groups.…”
Section: Organoleptic Parameters Of Broiler Chicken Fed Mlp and Abp I...contrasting
confidence: 99%
See 1 more Smart Citation
“…The inclusion of Moringa oleifera leaf powder and Allium sativum bulb powder into broiler chicken diet at the lowest level may not have the ability to affect the taste and aroma of the meat. This observation contrasted with the findings of Adomeh and Eguaoje (2019), who reported that high aroma score recorded in chicken thighs spiced with 1.5 % ginger and garlic easily influenced the broiler meat. The meat tenderness at the 8 th week was improved in T3 and T4 groups.…”
Section: Organoleptic Parameters Of Broiler Chicken Fed Mlp and Abp I...contrasting
confidence: 99%
“…Allium sativum bulb, Allium sativum bulb powder of dietary fibre, vitamin C and folic acid, as it contains calcium, iron and a low level of sodium with high protein quality. Adomeh and Eguaoje, (2019) reported that garlic has ability to soften the meat due to aromatic (organic) compounds it contained. This invariably increases the juiciness of the meat.…”
Section: Introductionmentioning
confidence: 99%